Smectite quantification in hydrothermally altered volcanic rocks. (May 2020) - Lévy, Léa; Fridriksson, Thráinn; Findling, Nathaniel; Lanson, Bruno; Fraisse, Bernard; Marino, Nicolas; Gibert, Benoit
Abstract: In volcanic environments, the presence of smectite may indicate recent hydrothermal circulations. Smectite is also responsible for enhanced rock electrical conductivity, as well as mechanical weakening. Therefore, quantifying smectite is important in geothermal exploration. Smectite identification requires X-ray diffraction (XRD) but quantification based on XRD is time-consuming and not always accurate. In the present study, we investigate the use of an optimized unbuffered Cation Exchange Capacity (CEC) determination, by back-titration of the Copper-triethylenetetramine(II) "Cu-trien" molecule, to quantify the smectite content of altered volcanic rock samples. We establish that a satisfying trade-off between the instrument uncertainty and an independant systematic error is theoretically reached for a fraction of reactants consumed of about 30% at the end of the exchange reaction. We suggest a modification to classical protocols to fall in that range. Finally, we show that optimized CEC determination by Cu-trien are a direct measure of the smectite weight fraction in altered volcanic samples, with an average CEC of pure smectite of 90 ± 5 meq/100 g.